STRATEGI PENYEDIAAN AIR BERSIH OLEH PAM JAYA DI RUSUNAWA SINDANG KECAMATAN KOJA JAKARTA UTARA MENUJU SUSTAINABLE DEVELOPMENT GOALS (SDGS) 2030 - Ramadhan, Madi; Prasetyo, Sisman (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2025)
This research discusses PAM Jaya's strategy in providing clean water in Rusunawa Sindang, North Jakarta, towards achieving the 2030 Sustainable Development Goals (SDGs). The research used a descriptive qualitative approach with data collection methods through interviews, observation, and literature review. The theory used was SWOT analysis according to Pearce & Robinson (2009). The research conclusion highlighted two main points. First, the strategic partnership strategy between PAM Jaya and universities and research institutions helps develop human resources and smart technology for operational efficiency and sustainability of water infrastructure. These partnerships not only strengthen PAM Jaya's technical capabilities but also generate innovations to sustainably improve the quality of water services, in accordance with SDGs 6. Secondly, the role of communities in providing clean water as active partners in the planning, management and maintenance of local water infrastructure is also important. Community participation ensures locally and culturally appropriate solutions, and strengthens local capacity to address environmental and social challenges. Thus, this thesis not only identifies PAM Jaya's strategy in meeting clean water needs in Rusunawa Sindang, but also shows how strategic partnerships and the role of communities can support the achievement of SDGs 2030, particularly related to universal access to clean water and sanitation.